Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To simplify the given expression [tex]\( \frac{6^{\frac{1}{3}}}{6^{\frac{10}{3}}} \)[/tex], we can use the properties of exponents, specifically the rule:
[tex]\[ \frac{a^m}{a^n} = a^{m - n} \][/tex]
In this case, the base [tex]\( a \)[/tex] is 6, [tex]\( m \)[/tex] is [tex]\( \frac{1}{3} \)[/tex], and [tex]\( n \)[/tex] is [tex]\( \frac{10}{3} \)[/tex]. Applying the rule:
[tex]\[ \frac{6^{\frac{1}{3}}}{6^{\frac{10}{3}}} = 6^{\frac{1}{3} - \frac{10}{3}} \][/tex]
Next, simplify the exponent:
[tex]\[ \frac{1}{3} - \frac{10}{3} = \frac{1 - 10}{3} = \frac{-9}{3} = -3 \][/tex]
So we have:
[tex]\[ 6^{\frac{1}{3} - \frac{10}{3}} = 6^{-3} \][/tex]
Now, express [tex]\( 6^{-3} \)[/tex] as a positive exponent by using the property [tex]\( a^{-b} = \frac{1}{a^b} \)[/tex]:
[tex]\[ 6^{-3} = \frac{1}{6^3} \][/tex]
Calculate [tex]\( 6^3 \)[/tex]:
[tex]\[ 6^3 = 6 \times 6 \times 6 = 216 \][/tex]
So:
[tex]\[ 6^{-3} = \frac{1}{216} \][/tex]
Therefore, the simplified form of [tex]\( \frac{6^{\frac{1}{3}}}{6^{\frac{10}{3}}} \)[/tex] is:
[tex]\[ \frac{1}{216} \][/tex]
The correct answer is [tex]\( \boxed{\frac{1}{216}} \)[/tex].
[tex]\[ \frac{a^m}{a^n} = a^{m - n} \][/tex]
In this case, the base [tex]\( a \)[/tex] is 6, [tex]\( m \)[/tex] is [tex]\( \frac{1}{3} \)[/tex], and [tex]\( n \)[/tex] is [tex]\( \frac{10}{3} \)[/tex]. Applying the rule:
[tex]\[ \frac{6^{\frac{1}{3}}}{6^{\frac{10}{3}}} = 6^{\frac{1}{3} - \frac{10}{3}} \][/tex]
Next, simplify the exponent:
[tex]\[ \frac{1}{3} - \frac{10}{3} = \frac{1 - 10}{3} = \frac{-9}{3} = -3 \][/tex]
So we have:
[tex]\[ 6^{\frac{1}{3} - \frac{10}{3}} = 6^{-3} \][/tex]
Now, express [tex]\( 6^{-3} \)[/tex] as a positive exponent by using the property [tex]\( a^{-b} = \frac{1}{a^b} \)[/tex]:
[tex]\[ 6^{-3} = \frac{1}{6^3} \][/tex]
Calculate [tex]\( 6^3 \)[/tex]:
[tex]\[ 6^3 = 6 \times 6 \times 6 = 216 \][/tex]
So:
[tex]\[ 6^{-3} = \frac{1}{216} \][/tex]
Therefore, the simplified form of [tex]\( \frac{6^{\frac{1}{3}}}{6^{\frac{10}{3}}} \)[/tex] is:
[tex]\[ \frac{1}{216} \][/tex]
The correct answer is [tex]\( \boxed{\frac{1}{216}} \)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.